The role of agrarian reform beneficiaries organizations (ARBOs) in agriculture value chain - Marife Magno-Ballesteros; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2020)
The objective of this paper is to evaluate how Agrarian Reform Beneficiary Organizations (or ARBOs) participate in the value chain; how they engage actors along the value chain and what challenges do they face in the process. Farmer organizations, such as ARBOs, are important conduits for smallholders to participate specifically in higher value chain. This strategy enables smallholders to pool resources, jointly carry out profitable activities, reduce risks and transaction costs and operate on scale economies. However, many farmer organizations in the country have low level of organizational maturity and are mainly formed to access funding. Thus, smallholder participation in higher value chain is limited; the gains from value chain initiatives would impact only on a modest number of smallholders' population and may not be sustainable in the long run. The paper suggests that farmer organizations and their participation in higher value chain can be improved by: one, enabling farmer members to commit to the organization through equity participation; two, enabling farmer organizations to establish enterprises that will generate income for members; and three, capacitating farmer organizations on building alliances/networking.
Keywords: 330; farmer organizations; value chain; ARBOs; agrarian reform; agriculture